Spatiotemporal changes in district-level carbon emissions in India, 2019–2024 - Arpit Shah; Rockli Kim; S. V. Subramanian (Global Sustainability, 2025)
Abstract Non-technical summary. India needs to balance carbon mitigation with its developmental priorities. The Indian district acts as an important administrative site where national- and state-level developmental and environmental policies are translated into ground-level implementation. In this work, we provide a replicable approach to analyze the evolution of district-level carbon emissions in near real-time. Our work shows that emissions are concentrated in a small number of districts, with this concentration increasing over time. We also find significant inter-district variation in the growth of emissions. We demonstrate the utility of high-resolution emissions data through three examples.